Plant-derived hydrogel and photosynthetic nano-units for myocardial infarction therapy - YongBo Lv; Dashuai Zhu; Junlang Li; Yuan Li; Chao Lu; Jianing Bi; Ke Huang; Shiqi Hu; Shuo Liu; Na Yan; Ke Cheng; Juan Wang (Nature Communications)
Abstract Ischemic injury and reperfusion injury collectively determine the total infarct size, a major prognostic factor following myocardial infarction (MI). Therefore, addressing both ischemic and reperfusion stages could substantially reduce infarct size and improve clinical outcomes. In this study, we develop a two-component therapeutic system from different parts of Glycyrrhiza: a functional hydrogel made from glycyrrhizic acid extracted from the stem and root, and nanosized chloroplast units (NCUs) derived from leaves. The hydrogel demonstrates therapeutic effects during both hypoxia and reoxygenation stages in vitro, while the photosynthetic NCUs alleviate hypoxia injury by providing ATP and NADPH under illumination. Subsequent in vivo study reveals the most significant therapeutic effect in the combination group (NCU plus hydrogel), which effectively treats both ischemic and reperfusion stages. Our study highlights the cross-species application of plant photosynthetic mechanisms in MI treatment and confirms that simultaneous treatment of ischemia and reperfusion is more effective than treating either stage alone, offering a promising therapeutic strategy for MI.